2020
DOI: 10.2217/fon-2020-0725
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns, Outcomes and Clinical Characteristics in Advanced Renal Cell Carcinoma: a Real-World US Study

Abstract: Aim: Assessing treatment patterns, outcomes and clinical characteristics in advanced renal cell carcinoma clinical practice. Materials & methods: A US cross-sectional physician survey conducted February–September 2019. Results: Surveyed physicians reported first-line treatment of 445 patients involving tyrosine kinase inhibitor monotherapy (51.0%), immuno-oncology (IO/IO combination) therapy (25.8%) or other regimens (23.1%). A total of 60.9% had physician-assessed IMDC risk. Of these 61.9, 50.9 and 27.6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…2 Traditional prognostic risk models like the IMDC classification are routinely used to inform upfront prognosis and treatment decisions to help predict patient outcomes in aRCC. 5 However, such prognostic estimates based on baseline risk factors were established in the era of single-agent tyrosine kinase inhibitors and cytokines, and do not adequately address outcomes for patients with aRCC who achieve a durable response and survival benefits with immunotherapy. 6,7 As the aRCC treatment landscape evolves and long-term outcomes continue to improve, an updated prognostic framework is needed.…”
Section: Introductionmentioning
confidence: 99%
“…2 Traditional prognostic risk models like the IMDC classification are routinely used to inform upfront prognosis and treatment decisions to help predict patient outcomes in aRCC. 5 However, such prognostic estimates based on baseline risk factors were established in the era of single-agent tyrosine kinase inhibitors and cytokines, and do not adequately address outcomes for patients with aRCC who achieve a durable response and survival benefits with immunotherapy. 6,7 As the aRCC treatment landscape evolves and long-term outcomes continue to improve, an updated prognostic framework is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Within the PRF, physicians were asked to provide the IMDC risk score (stated) for each patient based on the physician's subjective assessment; this also included the option for the physician to document if the IMDC score was not available in the chart or unknown. Additionally, IMDC risk criteria were collected for each patient so that the IMDC score could be independently calculated, as previously described [9]. Treatment at the time of data collection was categorized as TKI mono, IO mono, IO/IO comb and other therapies, with the latter comprising treatments such as IO therapy plus a targeted or chemotherapy agent and all other regimens not included in the three main groups.…”
Section: Outcomes and End Pointsmentioning
confidence: 99%
“…Current guidelines for advanced clear cell RCC advocate the use of first-line IO/IO and IO/TKI comb in patients with any International Metastatic RCC Database Consortium (IMDC) risk score; however, IO/IO comb is preferred for patients with intermediate or poor-risk scores [7]. The optimal sequence of regimens and their duration of use remain to be elucidated [7,8], as does the extent to which guideline-recommended therapy is implemented in routine clinical practice [9,10]. We have previously shown that guideline-recommended therapies were not widely prescribed in a study of treatment patterns in real-world clinical practice in patients with aRCC in the USA [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation